1999
DOI: 10.1016/s0002-9440(10)65362-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Metabolic Evidence for the Restricted Expression of Inducible Nitric Oxide Synthase in Healing Wounds

Abstract: Tissue injury initiates a temporally ordered sequence of local cellular and metabolic responses presumably necessary for successful repair. Previous investigations demonstrated that metabolic evidence for nitric oxide synthase (NOS) activity is detectable in woundsonly during the initial 48 to 72 hours of the repair process. Present results identify the cell types contributing inducible NOS (iNOS) to experimental wounds in rats. iNOS antigen was expressed in most macrophages present in wounds 6 to 24 hours aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 15 publications
2
57
1
Order By: Relevance
“…9 Current results differ from those reported previously from this laboratory in rat incisional wounds. 1 In those wounds, iNOS protein and the metabolic products of the NOS reaction (eg, citrulline) were detectable in wound cells and wound fluids during the initial, inflammatory phase of the repair process. The difference in the expression of iNOS in wound cells of rats and mice is probably explained by the relative promiscuity of expression of iNOS in rat versus mouse inflammatory cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…9 Current results differ from those reported previously from this laboratory in rat incisional wounds. 1 In those wounds, iNOS protein and the metabolic products of the NOS reaction (eg, citrulline) were detectable in wound cells and wound fluids during the initial, inflammatory phase of the repair process. The difference in the expression of iNOS in wound cells of rats and mice is probably explained by the relative promiscuity of expression of iNOS in rat versus mouse inflammatory cells.…”
Section: Discussionmentioning
confidence: 98%
“…Macrophages contributed the bulk of the iNOS protein to the wound, with the remainder found in polymorphonuclear leukocytes. 1 Based on such findings, it was proposed that NO generated by iNOS could participate in the regulation of the inflammatory phase of wound healing.…”
mentioning
confidence: 99%
“…Macrophages are known to be the major source of iNOS production during wound healing and their expression of iNOS is highest at the granulation tissue phase. 35 Macrophages have been implicated in all aspects of wound healing and angiogenesis. 36 During the granulation tissue phase, they are the predominant cell type and are responsible for production of cytokines and growth factors essential to the healing cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work from this laboratory demonstrated that inducible NO synthase is expressed exclusively by M in day 1 wound cell preparations (27). Because NO is known to induce apoptosis in target cells (28), its potential role in M-dependent PMN apoptosis was investigated.…”
Section: Coculture Of Day 1 and Day 5 Wound Cells Increases Pmn Apoptmentioning
confidence: 99%